Evolutionary history of Gymnocarpos (Caryophyllaceae) in the arid regions from North Africa to Central Asia. (26th May 2016) - Jia, Shu‐Wen; Zhang, Ming‐Li; Raab‐Straube, Eckhard V.; Thulin, Mats
Abstract : Gymnocarpos has only about ten species distributed in the arid regions of Asia and Africa, but it exhibits a geographical disjunction between eastern Central Asia and western North Africa and Minor Asia. We sampled eight species of the genus and sequenced two chloroplast regions ( rps 16 and psb B– psb H), and the nuclear rDNA (ITS) to study the phylogeny and biogeography. The results of the phylogenetic analyses corroborated that Gymnocarpos is monophyletic, in the phylogenetic tree two well supported clades are recognized: clade 1 includes Gymnocarpos sclerocephalus and G. decandrus, mainly the North African group, whereas clade 2 comprises the remaining species, mainly in the Southern Arabian Peninsula. Molecular dating analysis revealed that the divergence age of Gymnocarpos was c . 31.33 Mya near the Eocene and Oligocene transition boundary, the initial diversification within Gymnocarpos dated to c . 6.69 Mya in the late Miocene, and the intraspecific diversification mostly occurred during the Quaternary climate oscillations. Ancestral area reconstruction suggested that the Southern Arabian Peninsula was the ancestral area for Gymnocarpos . Our conclusions revealed that the aridification since mid‐late Miocene significantly affected the diversification of the genus in these areas.